Uji Efisiensi E-MagScience Berbasis Flip PDF Professional Tema Makanan dan Kesehatanku Untuk Menumbuhkan Kemampuan Berpikir Kritis Siswa SMP - Siti Najariah Sundari; Dwi Indah Suryani; Septi Kurniasih (PendIPA Journal of Science Education, 2022)
The E-MagScience product based on Flip PDF Professional on the theme of Food and Healthy to improve the critical thinking skills of junior high school students were made to obtain data efficiently. E-MagScience has supportive rubrics such as technology directing students to experiment with food tests. The superiority of E-MagScience puts interactive quizzes so students can answer directly through the media. The research methods used Research and Development, with the research and development model Borg and Gall (1983), which is adapted to the needs and abilities of researchers with restrictions on three stages, namely: the research and data collection stages, planning and developing a preliminary form of the product. Then this study shows the results of the validity of E-MagScience based on Flip PDF Professional based on validation by material experts achieving a score of 86% in the "Very Valid" category, validation by media experts achieving a percentage value of 90% in the "Very Valid" category and validation by experts the achievement of a percentage value of 90% in the "Very Valid" category. The efficiency level of E-MagScience reached a percentage value of 89% in the "Very Efficient" type.